Drosophila PS1 integrin is a laminin receptor and differs in ligand specificity from PS2. - Gotwals, P.J.; Fessler, L.I.; Wehrli, M.; Hynes, R.O. (Proceedings of the National Academy of Sciences of the United States of America, 1994)
We have expressed Drosophila position-specific (PS) integrins on the surfaces of Schneider S2 cells and tested for adhesion and spreading on various matrix molecules. We report that PS1 integrin is a laminin receptor and that PS1 and PS2 integrins promote cell spreading on two different Drosophila extracellular matrix molecules, laminin and tiggrin, respectively. The differing ligand specificities of these two integrins, combined with data on the in vivo expression patterns of the integrins and their ligands, lead to a model for the structure of integrin-dependent attachments in the pupal wings and embryonic muscles of Drosophila.